An Application for the Improvement of the Transportation System of the Flour in a Grain Mill using "PID Compact" - Eugen Răduca (Analele Universităţii "Eftimie Murgu" Reşiţa: Fascicola I, Inginerie, 2016)
The paper presents an application based on a PLC Simatic S7-1200, using the "PID_Compact" logical function, which can be used for the improvement of control systems. We also present a practical application: a system for the improvement of the transportation system of the flour in a grain mill using "PID Compact" .